2014
DOI: 10.1111/dmcn.12468
|View full text |Cite
|
Sign up to set email alerts
|

Motor development in 3‐month‐old healthy term‐born infants is associated with cognitive and behavioural outcomes at early school age

Abstract: MOSMotor optimality score MOL Motor Optimality List AIM To determine whether motor development at 3 months of age is associated with cognitive, motor, and behavioural outcomes in healthy children at early school age. METHODIn this cohort study, we included 74 term-born, healthy children (44 males, 30females; median gestational age 40.1wks, range 38.0-42.6wks). From video recordings (median 12.9wks, range 9.3-18.6wks), we assessed the quality of fidgety movements, and calculated a motor optimality score. At sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
60
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 27 publications
(52 reference statements)
6
60
1
1
Order By: Relevance
“…20 Recent studies have shown that optimal motor development in healthy infants is related to later cognition or language skills. 3,4 A common neural substrate is postulated to underlie the association between motor development in infancy and cognition at an older age. The basal ganglia, as part of the complex neural system of cerebral cortex-cerebellum-basal ganglia, have been traditionally known for motor control.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recent studies have shown that optimal motor development in healthy infants is related to later cognition or language skills. 3,4 A common neural substrate is postulated to underlie the association between motor development in infancy and cognition at an older age. The basal ganglia, as part of the complex neural system of cerebral cortex-cerebellum-basal ganglia, have been traditionally known for motor control.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer normal postural patterns are associated with lower intelligence at school age (Butcher et al., ). The absence of variable finger postures is associated with poorer visual–spatial perception at childhood (Hitzert, Roze, Van Braeckel, & Bos, ). Finally, the overall movement character of the infant is considered normal when it is smooth and fluent, and abnormal if it is monotonous, jerky, stiff, or cramped‐synchronized.…”
Section: The Quality Of Spontaneous Movements Of the Infantmentioning
confidence: 99%
“…The relationship between the age of achieving motor milestones in infancy and subsequent development has been investigated in various areas, such as cognitive, communication, and personal–social skills . Most such studies have targeted major gross motor milestones such as sitting, crawling on hands and knees, standing, and walking alone.…”
mentioning
confidence: 99%